Komunikasi efektif untuk transparansi dan akuntabilitas dalam penentuan bagi hasil pada pembiayaan musyarakah - khoir, Zalifatul khoir (Maliki Interdisciplinary Journal, 2025)
Communication plays an important role in the conceptual era, where innovation, productivity, and creativity are highly valued. With all the adequate and automatic facilities, competition is getting tighter in various aspects of life. Therefore, communication can be used as a tool for transparent transactions between parties in accounting. Transparency is a genuine and comprehensive openness, allowing active participation of the community in the management of public resources. The implementation of profit-based accountability and transparency has been carried out well in the responsibility to the guardian. In musharakah, a cooperation agreement between two or more parties for a particular business, each party contributes funds. Profits are divided based on agreement, while losses are borne according to the portion of the fund contribution. Effective communication ensures that all parties understand the terms of cooperation, so that transactions are carried out honestly and openly, increasing trust and good cooperation. In addition, good communication helps resolve conflicts that may arise, such as disagreements over profit sharing or fund management. In the digital era, communication technologies such as email, video conferencing, and online collaborative platforms strengthen transparency and accountability in musharakah. These technologies enable real-time communication, easy sharing of information, and documentation of decisions and actions. The application of appropriate communication technology increases the efficiency and effectiveness of musyarakah-based business cooperation, supporting the achievement of better and fairer common goals.